2021
DOI: 10.3389/fneur.2021.669703
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Long-Term Outcomes of Monotherapy and Polytherapy in Seizure-Free Patients With Epilepsy Following Antiseizure Medication Withdrawal

Abstract: Objective: The objectives of this study were to compare the risk and timing of seizure relapse in seizure-free patients with epilepsy following the withdrawal of monotherapy or polytherapy and to identify relevant influencing factors.Methods: Patients who had achieved at least a 2-year seizure remission and started the withdrawal of antiseizure medication (ASM) were enrolled in this study. All patients were followed for at least 3 years or until seizure relapse. According to the number of ASMs at the time of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…For instance, a study found no significant difference between monotherapy and polytherapy groups regarding complete blood count parameters, including leukocyte count, neutrophil count, lymphocyte count, hemoglobin level, and platelet count (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study found no significant difference between monotherapy and polytherapy groups regarding complete blood count parameters, including leukocyte count, neutrophil count, lymphocyte count, hemoglobin level, and platelet count (10,11).…”
Section: Discussionmentioning
confidence: 99%